Synthesis, Characterization, Docking and In Silico Pharmacokinetics Study of New Triazole Derivatives as TDP1 Enzyme Inhibitor Compounds - Abbas, Ali Hussein; Tawfeeq, Mostafa Fayez; Yousif, Emad Muthana (Tikrit Journal of Pharmaceutical Sciences, 2024)
Numerous research groups across the globe have been dedicatedly studying the mechanism involved in carcinogenesis and cancer progression focusing on developing various strategies for the prevention and treatment of cancer. Chemotherapy is a treatment used for the whole body to fight recurrent tumors using conventional anticancer drugs which can be made more effective by using chemosensitizers, which can decrease the required dosage for treatment. TDP-1 inhibitors have the potential to enhance the effectiveness of topotecan by increasing the sensitivity of tumors to the drug, both in laboratory and living organism settings. A new triazole derivatives were synthesized starting from Naproxen and Vanillic acid through multisteps reactions. The final compounds and their intermediates were monitored by chromatography (TLC) and characterized by 1HNMR. The final compounds were docked against the target TDP1 enzyme. The docking analysis for the titled compounds 5A and 5B revealed better binding affinity values against (TDP1 enzyme) target site compared with the reference (co-crystallized) ligand as well as they showed good ADMET and in silico toxicity profile.